2010
DOI: 10.1002/pon.1643
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐life and surgical treatments for rectal cancer—a longitudinal analysis using the California Cancer Registry

Abstract: Background-Heterogeneous results for research investigating health-related quality of life (HRQL) in patients undergoing sphincter-ablating procedures for rectal cancer are likely due to single institution experiences and measurement of HRQL. To address this heterogeneity, we evaluated HRQL in patients with rectal cancer by type of surgery, location of tumor and receipt of adjuvant therapy using an HRQL instrument that has not been used to address rectal cancer patients in a population-based sample over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 64 publications
(71 reference statements)
7
16
0
7
Order By: Relevance
“…Our results showed that younger and older patients had almost the same score of the overall QOL and its dimensions except emotional dimension which was lower in younger patients. It in line with the results of other studies which showed the poorer emotional performance of younger patients [9,21] . We found that females generally had poorer QOL than men, the same reported by Li et al [9] but some studies reported the lower social wellbeing score among men, that might be because they used different instrument for assessment of the QOL [21] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that younger and older patients had almost the same score of the overall QOL and its dimensions except emotional dimension which was lower in younger patients. It in line with the results of other studies which showed the poorer emotional performance of younger patients [9,21] . We found that females generally had poorer QOL than men, the same reported by Li et al [9] but some studies reported the lower social wellbeing score among men, that might be because they used different instrument for assessment of the QOL [21] .…”
Section: Discussionsupporting
confidence: 92%
“…At the time of this study we could not access to surgery profile of the patients, then the information about preserving sphincter was not available, however evidence showed that sphincter-ablating procedures do not necessarily reduce QOL in patients with rectal cancer [21] .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Participants in this study endorsed a range of negative physical symptoms, sexual problems, and body concerns. Physical symptoms were often highly prevalent, including urinary frequency, unintentional gas, frequent bowel movements or changes of ostomy bag, and dry mouth; while there was infrequent endorsement of pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…5 Evidence for differences in quality of life among patients by surgery type is mixed. 5,7 Few of these studies measured longitudinal changes in quality of life between treatment completion and early survivorship, and they typically did not include highly comorbid populations, such as U.S. Veterans. 8 These studies have demonstrated improvements in global quality of life over time 4,9 ; however, they have not typically looked at prevalence over time of CRC-specific symptoms, longitudinal differences among domains of CRC-specific quality of life, or the sociodemographic and clinical predictors of these differences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies showed that the presence of a stoma also has a major negative impact on the quality of life (Rispoli et al, 2009). However, other studies failed to show a statistically significant difference in the quality of life of patients who had stoma and those who underwent a sphincter-saving resection (Smith-Gagen et al, 2010;Campos-Lobato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%